Statement on the derivation of Health‐Based Guidance Values (HBGVs) for regulated products that are also nutrients - EFSA Scientific Committee (EFSA Journal, 2021)
Abstract This Statement presents a proposal for harmonising the establishment of Health‐Based Guidance Values (HBGVs) for regulated products that are also nutrients. This is a recurrent issue for food additives and pesticides, and may occasionally occur for other regulated products. The Statement describes the specific considerations that should be followed for establishing the HBGVs during the assessment of a regulated product that is also a nutrient. It also addresses the elements to be considered in the intake assessment; and proposes a decision tree for ensuring a harmonised process for the risk characterisation of regulated products that are also nutrients. The Scientific Committee recommends the involvement of the relevant EFSA Panels and units, in order to ensure an integrated and harmonised approach for the hazard and risk characterisation of regulated products that are also nutrients, considering the intake from all relevant sources.